2023
DOI: 10.3389/fmicb.2022.1104875
|View full text |Cite
|
Sign up to set email alerts
|

Intense pulsed light for inactivating planktonic and biofilm molds in food

Abstract: It has been reported that about a quarter of the world’s agriculture products is unable to be consumed each year because of mold contamination, resulting in incalculable economic losses. Despite modern food technology and the various preservation techniques available, the problem of mold contamination of food is still not adequately controlled. In this study, we simulated the biofilm formed by Aspergillus niger and Penicillium glaucum in liquid and solid food in 96 well cell culture plates and polycarbonate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
1
Order By: Relevance
“…Although temperature (4°C and 25°C) has been observed to impact the efficacy of IPL in killing P. aeruginosa under certain conditions, further research is needed to determine the generality of this effect. This result is inconsistent with our previous finding that temperature had no significant effect on bactericidal efficiency when IPL treated seven different food-borne Gram-positive bacteria and molds in food ( Li et al, 2023a , b ). Chen et al (2018 , 2020) found the best inactivation of Cronobacter sakazakii by IPL was achieved synergistically with a water activity of 0.25 and a residence time of 28 s with IPL at a temperature of approximately 57°C.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although temperature (4°C and 25°C) has been observed to impact the efficacy of IPL in killing P. aeruginosa under certain conditions, further research is needed to determine the generality of this effect. This result is inconsistent with our previous finding that temperature had no significant effect on bactericidal efficiency when IPL treated seven different food-borne Gram-positive bacteria and molds in food ( Li et al, 2023a , b ). Chen et al (2018 , 2020) found the best inactivation of Cronobacter sakazakii by IPL was achieved synergistically with a water activity of 0.25 and a residence time of 28 s with IPL at a temperature of approximately 57°C.…”
Section: Discussioncontrasting
confidence: 99%
“…( Xu et al, 2019 ). P. aeruginosa is frequently transmitted via the consumption of bottled or barrel water, leading to detrimental effects on human health ( Li et al, 2023a , b ). The Chinese National Standard for Natural Mineral Water for Drinking Purposes (GB8537-2008) and the National Food Safety Standard for Packaged Drinking Water (GB19298-2014) specify that P. aeruginosa is “not detectable.” Because it can survive and proliferate in water, P. aeruginosa is easy to cause secondary contamination.…”
Section: Introductionmentioning
confidence: 99%
“…2 Infections caused by microorganisms oen lead to irreversible damage and immeasurable losses. 3,4 Generally, the use of antimicrobial agents is an effective and important approach in combating microbial threats and controlling the growth of bacteria on the surfaces of materials. Bacteria can be categorized as Gram-positive (G+) or Gram-negative (G−) based on the Gram staining method.…”
Section: Introductionmentioning
confidence: 99%